Widening the tool set for breeding superior banana cultivars. Can new techniques of pollen handling and pollination help overcome the lack of recombinant seed in banana breeding? - Ralf Bodo Trognitz (Reproduction and Breeding)
Pollen tube growth (PTG) monitoring was applied to florets of domesticated bananas and plantains. Observations were made in UV microscopy after Aniline Blue staining specific for callose, a carbohydrate of pollen tubes. It was found that total pollen grain numbers on a stigma and total pollen tubes developing after sufficient time for growing to reach the ovules within a female floret ranged from nil to few. This suggested the standard hand pollination technique, HP, may be insufficient to achieve desired pollination quality and respective fertilization for seed development. Pollen deposition and pollen tube growth was at least ten times larger when applying the newly developed pollen-anther-stigma, PAS, technique of pollination. This PAS technique includes mechanically working wilted anther pieces holding and exposing the pollen into the female stigma. PAS provided the potential for maximum seed formation depending on genetic limitations that may be present. PAS is therefore recommended for use in investigations of reproductive processes, such as sterility and self-incompatibility, and it can help increasing the production of recombinant seeds in planned crosses for breeding and selection.